1994
DOI: 10.1007/bf00188614
|View full text |Cite
|
Sign up to set email alerts
|

HLA supratypes in an Italian population

Abstract: A supratype analysis of a North Italian population was performed, using 16 polymorphisms in the HLA region spanning the HLA-A-DP segment. Fourteen supratypes were identified, mostly corresponding to those found in other Caucasoid populations. The degree of their conservation both within the B-DR/DQ region and in the regions telomeric and centromeric from HLA-A and DP was evaluated and linkage disequilibria among several DR and DP alleles were identified. Notably, the degree of association with DP increased whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Among the alleles at the other tested loci known to be carried by the B8‐DR3 extended haplotype (13,25), DRB3*0101, TNFa2 and MOGc‐148 were also preferentially transmitted to the patients (OR > 1), but did not reach statistical significance (Table 3, Fig. 2A); conversely, D6S265‐126 and D6S2223‐172 showed the same frequency in DR3‐T and DR3‐NT haplotypes.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Among the alleles at the other tested loci known to be carried by the B8‐DR3 extended haplotype (13,25), DRB3*0101, TNFa2 and MOGc‐148 were also preferentially transmitted to the patients (OR > 1), but did not reach statistical significance (Table 3, Fig. 2A); conversely, D6S265‐126 and D6S2223‐172 showed the same frequency in DR3‐T and DR3‐NT haplotypes.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast with markers of the B8‐DR3 haplotype, alleles and allele combinations characterizing the B18‐DR3‐extended haplotype (namely DRB3*0202, TNFa1, MICA‐A4, MICB‐CA14, MIB326; 13,14,24), were less frequently present in DR3‐T vs DR3‐NT haplotypes, thus reducing the CD risk conferred by DR3/DQ2 (Table 4). These results did not reach statistical significance because of the low number of B18‐DR3 haplotypes conserved telomeric of DRB3 (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacking direct information from family data, which were available only for CCHB mothers, haplotypes were deduced from population data following a commonly used procedure (29,30). For example, first, we calculated associations of DRB1 alleles with alleles at DQA1 and DQB1 loci in the control population.…”
Section: Methodsmentioning
confidence: 99%
“…(4)), linkage disequilibria between DWDQ and DP loci HLA-DP loci appear generally to be weak (5) or even absent (4,6). Several studies have reported on DPA1-DPBl linkage in Caucasian populations (7)(8)(9) and phenotypic DP combinations have been described as factors associated with particular infections in Ah5cans (10,11). Most earlier studies on HLA DPAl and DPBl alleles have focused on two DPAl alleles only, namely DPA1*0103 (previously DPAl*Ol) and DPA1*0201 (DPA1*02).…”
mentioning
confidence: 99%